2000
DOI: 10.4049/jimmunol.165.12.7234
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of the IL-12 Receptor β2 Chain in Crohn’s Disease

Abstract: Crohn’ s disease (CD) is a chronic intestinal inflammatory disorder characterized by aberrant mucosal Th1 cell activation and production of IL-12, the major Th1-driving factor. The T cell response to IL-12 is dependent on the expression of a specific receptor composed of two subunits, termed IL-12Rβ1 and IL-12Rβ2. The content of IL-12Rβ2, as measured at the mRNA level, is crucial in regulating Th1 differentiation. In this study we therefore investigated IL-12Rβ2 RNA transcripts in CD. IL-12Rβ2 expression was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 39 publications
3
59
0
Order By: Relevance
“…The deleterious effects of continued IL-12 signaling are evident in inflammatory disorders such as Crohn's disease (45). Therefore uncontrolled responses to IL-12 may contribute to the severe inflammatory disease in SOCS-1 Ϫ/Ϫ mice.…”
Section: Resultsmentioning
confidence: 99%
“…The deleterious effects of continued IL-12 signaling are evident in inflammatory disorders such as Crohn's disease (45). Therefore uncontrolled responses to IL-12 may contribute to the severe inflammatory disease in SOCS-1 Ϫ/Ϫ mice.…”
Section: Resultsmentioning
confidence: 99%
“…In active Crohn's disease, the expression of IL-12 receptors on mucosal cells is increased (5). Various immunohistological studies indicate that in situ IL-12 is overproduced by macrophages in Crohn's disease, and that macrophages isolated from the inflammatory lesions of patients with Crohn's disease produce increased amounts of IL-12 ex vivo (6).…”
Section: Introductionmentioning
confidence: 99%
“…Qingdong Guan, 1,2 Yanbing Ma, 2 China-Li Hillman, 2 Gefei Qing, 3 Allan G Ma, 1,2 Carolyn R Weiss, 1,2 Gang Zhou, 2 Aiping Bai, 2 Richard J Warrington, 4 Charles N Bernstein, 4,5 and Zhikang Peng with the downregulation of a broad array of inflammatory cytokines and chemokines in the colon (14). Recently, a genome-wide association study has reported IL-23R as an IBD gene that is highly associated with Crohn's disease (15).…”
Section: Targeting Il-12/il-23 By Employing a P40 Peptide-based Vaccimentioning
confidence: 99%
“…The IL-12R ␤2 chain has been shown to be selectively expressed on Th1 cells, whereas the ␤1 chain is present on both Th1 and Th2 cells (35,36). Expression of IL12R ␤2 is up-regulated in diseases characterized by a Th1-skewed immune status (37,38). Cytokines that further characterize a Th1-driven immune response are IFN-␥ and TNF-␣.…”
Section: Lymphocytic and Th1 Response Toward Infection With Differentmentioning
confidence: 99%